Explosive Power Training of Leg Muscles Using the Plyometric Depth Jump Model for Kediri City Athletic Athletes - Dwinda Abi Permana; Rendhitya Prima Putra; Dwi Kurnia Shandy (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Athletics is one of the most measured sports and is the mother of sports of all other sports. Athletics is divided into several parts according to its specialization numbers including running, horizontalvertical jump, and rotational linear throwing. Athletics is predominantly a measurable sport that combinesseveral physical biomotor components including speed, strength, endurance, explosive power, andcoordination in order to achieve optimal achievement targets. Kediri City itself is a city that is included inthe barometer of athletic development in East Java and even nationally, as evidenced by severalcompetitions in various age categories (pre-teens, teens, and seniors) which always come out as overallchampions or there is an athletic delegation from Kediri City who participates in the Sea Games, AsianGames, to the Olympic Games. In a smaller scope of development, in KONI Kediri City there are severalsuperior sports branches, of which athletics is one of them and is always a gold medal barn in everyimplementation of the East Java provincial sports week. Explosive power training development has avery important role for athletic athletes, this is because almost 80% of athletic competition numbersrequire explosive power as a determinant of success in achieving targeted achievements. Thiscommunity service was carried out with the aim of seeing the level of explosive power of Kediri City'sathletic athletes by holding explosive power training activities for the lower body extremities (legs).